Participação social: reflexões teórico-conceituais e práticas entre e com terapeutas ocupacionais - Silva, Ana Cristina Cardoso da (2021)
Occupational therapists have invested in studies to assess and deepen knowledge about theoretical-methodological perspectives and theoretical-practical references that delimit specificity and draw the identities of the profession in society, which influences the production of care and discussions about the terminologies used. Social participation is one of the concepts used and can be present in professional practice. In a bibliographic survey, it was confirmed that there are different understandings (converging or not) about social participation in different areas. Consequently, it was assumed that there could be more points of view worked on by occupational therapy, which attributed other meanings and senses. For this reason, the main purpose of this research were: to identify and analyze the concepts of occupational therapists about social participation in their fields of knowledge and practice, and to contribute with a critical reflection on the theme in the context of occupational therapy. As specific aims: to identify the theoretical references on social participation that are used and produced by occupational therapists; to identify the work methodologies developed by occupational therapists to enable concrete forms of social participation of the population; to reflect on the possibilities, limits and challenges for the construction of social participation in the context of the practice of occupational therapists. From a collaborative research methodology and based on the critical perspective, occupational therapy teachers and professionals, active in the state of São Paulo, were invited to answer a questionnaire and Delphi technique, both in the online form. The questionnaire characterized the professionals and their practices in teaching, researching, activities with community, and assistance and Delphi technique sought to establish a consensus on the definition of social participation. In the consultation phase of the Delphi technique, the professionals wrote their conceptions about social participation and, in the consensus phase, freely expressed their opinions and judgments, in order to, in a collective and collaborative construction, adopt a definition of social participation. In the first round of the consensus phase, 38 teachers and 27 professionals participated and in the second round, 20 and 14, respectively. According to the proceedings of the Delphi technique, part of the results was analyzed quantitatively, through the establishment of degrees of agreement for the conceptions arranged in affirmatives. Then, six categories of analysis were built, which identified the multiple ways of understanding, defining and building social participation in different fields of professional insertion: I. Social participation and social interactions, II. Social participation and movement: beyond coming and going, III. Social participation as a political practice, IV. Social participation: between an occupation and human activities, V. Social participation and the processes of social inclusion and insertion and VI. Social participation in the fields of knowledge and practice in occupational therapy. The thesis was concluded with six definitions: social participation as social interactions; as circulation, as engagement in public and political life, as a daily activity and related to engagement in activities, as a theoretical framework and as an objective and tool for practice. The use and views on social participation were found to be also related to the different fields of activity, teaching, research and activities with communities, the ways and methodologies of work, the population, their contexts of life, demands and needs. On the other hand, it was found that there were some weaknesses regarding the theoretical basis and the indiscriminate use of the concept.